A combined pool/bilateral dispatch model for electricity markets with security constraints (2011)
ABSTRACT: The secure operation of the electric power system is a challenging task for the system operator which is responsible of its coordination, control and monitoring. In most power systems security is typically handled on a multi–state approach. In which case, security criteria are incorporated by means of additional constraints, modifying the initial dispatch calculation. In this paper a generation dispatch model for competitive energy markets considering security constraints is presented. The proposed approach combines the generation dispatch related to pool and bilateral markets with coupled post–contingency optimal power flows into a single optimal dispatch model, avoiding economic inefficiencies that appear in conventional multi–stage dispatch approaches. The proposed model is linear, and as such, it is based on a DC model of the network. A 6–bus didactic system and the IEEE RTS–24 bus test system are used in order to show the operation and effectiveness of the proposed approach and to compare it with the basic pool/bilateral dispatch with no security constraints. Results show that the inclusion of security constraints lead to a higher dispatch cost. Furthermore, it was found that the enforcement of firmed bilateral contracts might lead to system congestion.